Analysis of radical formation by EPR in complex starch-protein-lipid model systems and corn extrudates. (30th November 2020) - Amft, Jonas; Steffen-Heins, Anja; Schwarz, Karin
Highlights: Stable and short-lived radicals are formed in starch-protein-lipid systems. PBN adduct, hydroperoxide and hexanal formation correlate in model systems. Spectra simulation identifies alkoxyl radical adducts as major short-lived radicals. Extrusion cooking promotes formation of stable protein radicals. Abstract: The formation of short-lived and stable radicals was investigated using electron paramagnetic resonance (EPR) spectroscopy and compared with hydroperoxides and hexanal in complex starch-protein-lipid model systems, as well as in corn extrudates. Stable radicals were detected directly in ground samples. Short-lived lipid radicals were measured ex situ in ethyl acetate extracts of model systems and extrudates by the use of the spin trap PBN. Significant adduct formation was found after 30 min at 50 °C. During storage, lipid radicals (PBN adducts) increased in model systems. Simulation of EPR spectra from bulk oil demonstrated that mainly alkoxyl radical adducts were detected, to which rapidly decomposing peroxyl radical adducts also contributed. Stable radicals in extrudates were attributed to protein radicals based on g-value of 2.00467 compared with 2.00474 found in model system prepared with zein. The signal intensity of the stable radical remained constant during storage, but increased during extrusion.